Unité Centralisée de Reconstitution des Cytotixiques (URCC) - Habi , Souhila; Saffari , Fadila; Berretil , Rima; ALLEL (Encadrant) (Université Sétif1 Ferhat Abbas. Faculté de Médecine. Déppartement de Pharmacie, 2023)
The préparation of cytotoxic drugsis a delicate and demanding task due to their potential toxicity. Pharmaceutical grade is essential to ensure that, these drugs are prepared, handled, and administered safely. Qualified personnel and specialized equipment are required. To achieve this, the establishment of a Centralized Cytotoxic Reconstitution Unit (UCRC) is the ideal solution. In our work, we first presented the recommendations provided by the standards relating to Good Practices for the Preparation of Cytotoxics. We then drew up a set of specifications that identified the prescription, the preparation procedures, the personnel, the premises and the equipment. We also explained the risks of preparing anticancer drugs and protective measures
Keywords: Cytotoxiques; Bonnes Pratiques de Préparation; Unité de préparation centralisée.